2015
DOI: 10.1097/nen.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Smooth Muscle Contractility by Competing Endogenous mRNAs in Intracranial Aneurysms

Abstract: Alterations in vascular smooth muscle cells (SMCs) contribute to the pathogenesis of intracranial aneurysms (IAs), but the genetic mechanisms underlying these alterations are unclear. We used microarray analysis to compare tissue small noncoding RNA and messenger RNA expression profiles in vessel wall samples from patients with late-stage IAs. We identified myocardin (MYOCD), a key contractility regulator of vascular SMCs, as a critical factor in IA progression. Using a multifaceted computational and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…This indicates there will be ongoing revision of the human genome as previously annotated lncRNAs emerge as mRNAs. Whether encoding a peptide or not, it seems that a noncoding function of any transcript can no longer be ignored [215, 229]. Finally, it will be important to determine whether any relevant SNPs exist in a putative lncRNA using LincSNP (http://210.46.85.180:8080/LincSNP/search.jsp) [230] or lncRNASNP (http://bioinfo.life.hust.edu.cn/lncRNASNP/) [231].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates there will be ongoing revision of the human genome as previously annotated lncRNAs emerge as mRNAs. Whether encoding a peptide or not, it seems that a noncoding function of any transcript can no longer be ignored [215, 229]. Finally, it will be important to determine whether any relevant SNPs exist in a putative lncRNA using LincSNP (http://210.46.85.180:8080/LincSNP/search.jsp) [230] or lncRNASNP (http://bioinfo.life.hust.edu.cn/lncRNASNP/) [231].…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies were performed in dogs. Almost half of the mouse models were employed in transgenic animals [22,41,43,53,92,95,96,99,102,105,106,109,112,114,127].…”
Section: Resultsmentioning
confidence: 99%
“…We chose MYOCD and miR-9 as a model system because: 1) miR-9 was reported to be differentially expressed in IA SMCs in comparison to the normal control [27]; 2) it has been confirmed that MYOCD is essential in the process of enhancing contractility of vessels by expressing a unique group of signaling molecules, contractile agonist receptors, and contractile proteins to fulfill the task [28,29]; 3) delicate expression level change of MYOCD was critical in determining percentage of survival and IA was demonstrated by the IA mouse model [30]; and 4) partial or complete loss of MYOCD can lead to dramatic deceleration of IA in the IA mouse model [13]. …”
Section: Discussionmentioning
confidence: 99%
“…SMC contractile assay was used to determine the contractility of SMCs with different treatments, as previously described [13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation